Early Intervention and Strategies to Build a Friendly Ecosystem for Children with Attention Deficit Hyperactivity Disorder - Marlina, Lini; Nugroho, Jatmiko Wahyu; Junaidi, Ahsan Romadlon; Novianti, Ranti; Ediyanto, Ediyanto (Jurnal ORTOPEDAGOGIA, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder prevalent in children, which impacts their cognitive and behavioral functioning. Early intervention is critical in managing ADHD and improving long-term outcomes. This article summarizes current research on early intervention for ADHD children using a scoping literature review method, focusing on the assessment, treatment and effectiveness of various interventions. The research reviewed highlights the importance of early identification and intervention in reducing the challenges associated with ADHD. Strategies such as mindfulness-based interventions, cognitive training, and behavioral therapy show promise in improving symptoms and functioning in children with ADHD. In addition, the role of parents and clinicians in supporting children with ADHD through interventions was also emphasized, in addition to the role of social media that provides positive support will form a friendly ecosystem for children with ADHD. Overall, early intervention and strategies play an important role in meeting the needs of children with ADHD and improving their well-being.